2011
DOI: 10.1177/1359105311421050
|View full text |Cite
|
Sign up to set email alerts
|

Promoting positive motherhood among nulliparous pregnant women with an intense fear of childbirth: RCT intervention

Abstract: This RCT intervention among nulliparous pregnant women with an intense fear of childbirth sought to promote preparedness for childbirth and to enhance positive parenting. Pregnant women (n = 8,611) filled in a 'fear of childbirth' questionnaire. Nulliparous women with severe fear of childbirth (n = 355) were randomized into intervention (n = 131; 41 refused) and control (n = 224) groups. They rated themselves on a preparedness scale in middle and late pregnancy, and on a motherhood scale three months after chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 40 publications
1
57
0
1
Order By: Relevance
“…Previous randomised controlled studies have shown appropriate counseling of FOC to be successful, as women in the study groups reported more positive birth experiences and underwent CS less frequently than controls. 29,30 However, FOC was associated with 3.3-and 4.5-fold higher rates of CS among nulliparous and multiparous women, respectively (increases from 19 to 45.4% and 11.9 to 37.2%, respectively). Smaller population-based studies have reported increases in CS rates of the order of 30% among women with FOC.…”
Section: Discussionmentioning
confidence: 93%
“…Previous randomised controlled studies have shown appropriate counseling of FOC to be successful, as women in the study groups reported more positive birth experiences and underwent CS less frequently than controls. 29,30 However, FOC was associated with 3.3-and 4.5-fold higher rates of CS among nulliparous and multiparous women, respectively (increases from 19 to 45.4% and 11.9 to 37.2%, respectively). Smaller population-based studies have reported increases in CS rates of the order of 30% among women with FOC.…”
Section: Discussionmentioning
confidence: 93%
“…Women described that information was not provided routinely and they had to seek it actively, which is disappointing given the number of studies showing that education of all women in the antenatal period (including those with a previous CS) improves birth outcome (Maimburg et al, 2010) and is appreciated and requested by nulliparous and multiparous women alike (Mungrue et al, 2010). For example, relaxation and birth preparation classes, which have led to a reduction in CS rates in nulliparous women (Khunpradit el al., 2011), and psycho-educational group sessions for women experiencing an intense fear of childbirth (Salmela-Aro et al, 2012) could also be tried with women following previous CS.…”
Section: Introductionmentioning
confidence: 99%
“…The women in the psychoeducation group also had fewer depressive symptoms postpartum and a better maternal adjustment than the women in the control group. In an additional study from this trial, Salmela-Aro et al (2012) showed that the intervention increased the preparedness for the transition to motherhood and the motivation to parenthood among women with severe FOC in the psycho-educational group compared with the control group. The increased preparedness for the transition to parenthood was seen as a mediator between the observed decrease of FOC (W-DEQ A sum score) and the later experience of a positive parenthood (measured with the Maternal Adjustment and Maternal Attitudes Scale, MAMA) (SalmelaAro et al 2012).…”
Section: Current Knowledge Of Interventions With Therapeutic Elementsmentioning
confidence: 99%